(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In data-sparse locations, the necessity for the integration of remote sensing and in-situ-based approaches in assessing greenhouse gases cannot be overstressed. Akin other countries in sub-Saharan Africa (SSA), Nigeria is yet to leverage on and fully maximize the potentialities offered by satellite remote sensing in monitoring and assessment of biophysical and ecological change indicators including greenhouse gases. This study was undertaken with the prime motivation of ascertaining the variations of greenhouse gases concentrations in Delta State, Nigeria as well as the correlation between in-situ measurement and satellite remote sensing observation. Datasets comprising carbon monoxide (CO), nitrogen dioxide (NO2) and sulfur dioxide (SO2) and were sourced from the archive of the European Space Agency and field sampling using Aeroqual S500 ambient air analyser. Descriptive statistics, independent Samples t-Test, analysis of variance (ANOVA), Tukey HSD test of multiple comparisons and simple linear regression (SLR) were the major inferential statistical frameworks used in the study. The results showed that greenhouse gases exhibited statistical significant spatial variability with the non-fictional variation of CO from In-situ measurement domiciled between Delta South Senatorial District (SD) and Delta North SD with Mean Difference of – 0.05 (p-value of 0.027 < 0.05). Validity, extent of accuracy and reliability of remotely-sensed greenhouse gases with in-situ observations was also established with CO, SO2 and NO2 in Delta South SD being statistically significant at 95% confidence level. The paper recommends the adoption of space-borne satellite remote sensing resources and GIS in periodic monitoring, mapping and assessments of environmental change indicators.